Legal Protection of Drivers in Train Accidents at Crossings Without Door Bars - Faniyah, Iyah; Adhiyaksa, Fagher (Master of Law Program, Ekasakti University, 2023)
Legal Protection for Machinists in Train Accidents at Crossings Without Door Bars in the Area of PT. Kereta Api Indonesia Persero Divre West Sumatra is based on Article 124 of Law Number 23 of 2007 concerning railways. PT KAI provides protection to machinists by being responsible if third parties can prove from the chronological results of investigations and investigations if it is proven that the machinist really made a mistake that resulted in an accident and caused casualties. Form its legal liability by insuring losses suffered by third parties. In train accidents at crossings without door bars, machinists are not given responsibility alone but are protected by the company. The legal responsibility of PT Kereta Api Indonesia Persero Divre West Sumatra to victims of train accidents at crossings without door bars is that the security and safety of public road users is not the responsibility of the transportation organizing body, in this case PT. (Persero) Indonesian Railways. The crossing gate bars are not for the security of public road users, but to secure and facilitate train travel alone. Criminal liability by the machinist for train accidents must be seen from the element of guilt and also see the responsible ability of a machinist, if all elements have been fulfilled then the machinist can be held responsible for train accidents. When crossing a crossing, it also bears the risk that if the crossbar is not provided as an adequate facility in limiting road users from passing and allowing the train to pass first.